Functional endoscopy in neurogenic dysphagia: a feasibility study focusing on the esophageal phase of swallowing - Rückert, Jan; Lenz, Philipp; Heinzow, Hauke; Wessling, Johannes; Warnecke, Tobias; Herrmann, Ingo F.; Strahl, Michael; Lenze, Frank; Nowacki, Tobias; Domagk, Dirk (Endoscopy International Open, 2021)
Background and study aims Due to demographic transition, neurogenic dysphagia has become an increasingly recognized problem. Patients suffering from dysphagia often get caught between different clinical disciplines. In this study, we implemented a defined examination protocol for evaluating the whole swallowing process by functional endoscopy. Special focus was put on the esophageal phase of swallowing.Patients and methods This prospective observational multidisciplinary study evaluated 31 consecutive patients with suspected neurogenic dysphagia by transnasal access applying an ultrathin video endoscope. Thirty-one patients with gastroesophageal reflux symptoms were used as a control group. We applied a modified approach including standardized endoscopic positions to compare our findings with fiberoptic endoscopic evaluation of swallowing and high-resolution manometry. The primary outcome measure was feasibility of functional endoscopy. Secondary outcome measures were adverse events (AEs), tolerability, and pathologic endoscopic findings.Results Functional endoscopy was successfully performed in all patients. No AEs were recorded. A variety of disorders were documented by functional endoscopy: incomplete or delayed closure of the upper esophageal sphincter in retroflex view, clearance disturbance of tubular esophagus, esophageal hyperperistalsis, and hypomotility. Analysis of results obtained with the diagnostic tools showed some discrepancies.Conclusions By interdisciplinary cooperation with additional assessment of the esophageal phase of deglutition using the innovative method of functional endoscopy, the diagnosis of neurogenic disorders including dysphagia may be significantly improved, leading to a better clinical understanding of complex dysfunctional patterns. To the best of our knowledge, this is the first study to show that a retroflex view of the ultrathin video endoscope within the esophagus can be safely performed. [NCT01995929]